PENGEMBANGAN INSTRUMEN EVALUASI YANG HOLISTIK KELAS XI IPA SMA - Fitriyeni, Fitriyeni (Perspektif, 2017)
Evaluation instrument is a holistic assessment tool for learners to acquire information in accordance with the standards of competence and basic competences that should be possessed by learners. The evaluation instruments include cognitive, affective, and psychomotor domain. This research is a developmental research of 3 D 4 D model (Four-D Models). The development process is carried out as follows: 1) definition, 2) design, 3) development. Test subjects were students of SMAN 1 Pekanbaru class XI Science. The data of this study is primary data consists of the results of the validation instruments, instrument reliability, and the practicalities of the instrument. Data were analyzed with descriptive analysis in the form of a percentage. The results showed that the instrument is very valid and practical evaluation. Evaluation instruments in are the form of written tests, performance assessments of cognitive, affective performance, psychomotor performance assessment, project assessment, product assessment, self-assessment, an assessment of learners, journal / notes educators..